FACTORS AFFECTING THE COMPLETION OF COMPLETE BASIC IMMUNIZATION IN INFANTS IN THE WORKING AREA OF THE JEULINGKE COMMUNITY HEALTH CENTER, BANDA ACEH CITY IN 2020 - Marzuki, Marzuki; Jannah, Mifthahul; Mawardi, Mawardi (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Aceh, 2022)
Background: Basic immunization is a mandatory health program held by the government for infants aged 0-12 months as immunity against diseases that can be prevented by immunization. The results of the initial data tracing at the Jeulingke Health Center in Banda Aceh City in 2019, showed that one village had reached the UCI, namely 20% and 80% of the villages had not yet reached the UCI. The aim of this study was to determine the factors that influence the completeness of complete basic immunization in infants in achieving Universal Child Immunization (UCI) in the working area of the Jeulingke Health Centre, Banda Aceh in 2020. Methods: This study is a descriptive analytic study with a cross sectional design. Sampling using proportional sampling method as many as 81 mothers who have babies 9-12 months. Data analysis used the Chi Square test. Results: The results showed that infants who were given complete immunization were 45.7% and those who were incomplete were 54.3%. The bivariate analysis showed that there was a relationship between knowledge (p-value 0.001), family support (p-value 0.001), the role of health workers (p-value 0.025), and the issue of illicit immunization (p-value 0.046) with the completeness of basic immunization in infants. Conclusion: It is hoped that Puskesmas officers can conduct counseling in the community to increase mother's knowledge about the benefits of complete basic immunizations for babies and it is hoped that mothers should immunize their children on time, considering that immunization is very important to equip their children with health in the future.